A double network hydrogel electrolyte-based electrochromic device for enhanced electrochromic performance and lower power consumption. (April 2023) - Pan, Ming-yue; He, Qi; Liu, Jia-ning; Du, Kui; Gong, Cheng-bin; Tang, Qian
Abstract: This study aims to investigate the electrochromic behavior of a Y-shaped, water-soluble monosubstituted viologen analog, BPYDB-C6 H13, in different electrolyte systems. Two all-in-one gel-type ECDs (CMC-Na-ECD and CMC-Na-PAM-ECD) with CMC-Na hydrogel and CMC-Na-PAM double network hydrogel as the electrolytes and a solution-type ECD (DIW-ECD) were fabricated, and the electrochromic behaviors of BPYDB-C6 H13 in different electrolytes were studied. Compared to DIW-ECD, the gel-state ECDs, especially CMC-Na-PAM-ECD with double network channel, showed enhanced cycling stability (retaining of the initial optical contrast after 12, 000 s: 99.0% versus 95.5%), improved coloration efficiency (168.5 cm 2 /C versus 64.3 cm 2 /C), lower power consumption (0.55 mW/cm 2 versus 2.11 mW/cm 2 ), and longer memory time, because CMC-Na-PAM hydrogel had a larger pore size and a smoother transfer path than CMC-Na, thus reduced the path of charge transfer, and enhanced the ionic conductivity. The characteristics of easy-to-make, better electrochromic performance, and ultra-low power consumption make this gel-state ECD a promising candidate for applications in the fields of electronic paper, smart windows, displays, etc. Graphical abstract: Image 1 Highlights: CMC-Na and CMC-Na-PAM are used as the gel electrolytes for electrochromic devices. Gel electrolytes are beneficial to improve cycling stability and coloration efficiency. ECDs based on gel electrolytes show lower power consumption and longer memory time. CMC-Na-PAM-ECD with double network channel performs better than CMC-Na-ECD.